Inclusive Education in Elementary Schools in Pandeglang District: Challenges and Accessibility Strategies for Children with Special Needs - Ratna Dewi; Soleh Hidayat; Aan Hendrayana (Jurnal Penelitian Pendidikan IPA, 2025)
Inclusive education is a learning system that aims to provide equal education services for all children, including children with special needs (ABK). This study aims to examine the challenges faced by Elementary Schools in Pandeglang Regency in implementing inclusive education and strategies to increase accessibility for children with special needs. Parental support in the learning process of children at home, as well as social acceptance in the surrounding environment, greatly determine the sustainability of education for children with special needs. In addition, partnerships between schools and local communities are effective strategies in building a friendly, inclusive, and participatory learning environment. Therefore, integration between policy approaches, teacher capacity development, and community empowerment is an important foundation in building a sustainable inclusive education system. The method used is descriptive qualitative with data collection through observation, interviews, and document analysis. The findings show that the limited number of trained educators, minimal facilities and infrastructure, and social stigma are the main obstacles, as well as the high number of children who do not attend school. The strategies implemented include teacher training, partnerships with parents and social institutions, and the use of adaptive learning technology. The research recommendations emphasize the need for policies to support inclusion and strengthen school capacity in serving children with special needs (ABK).